LECTURER TEACHING STRATEGY TO FORM THE CHARACTER OF STUDENTS AS PROSPECTIVE PRIMARY TEACHER IN SOUTH PAPUA - Nirtha, Eva; Ruma Bay, Rudolfus; Tekdi Nainggolan , Herrio (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the teaching strategies applied by elementary school teacher education lecturers in shaping the character of prospective teachers in South Papua. The research method used is a qualitative method with a descriptive approach. Data collection techniques through in-depth interviews, observations, and documentation. Data analysis was carried out by comparing lecturers' strategies in teaching and using previous studies to support qualitatively described findings data. The results of this study show that there are various kinds of teaching strategies by lecturers to form the character of prospective teachers, including teaching strategies using project-based learning models, writing reflections, and including character values in learning planning and the creation of learning media. A comparison between teaching strategies and previous findings shows that the formation of student character of prospective teachers, especially the character of responsibility, confidence, discipline and empathy of students, occurs through the innovation of lecturers' teaching strategies, including the inclusion of character in the lecturer's semester learning plan. These findings emphasize the importance of the role of lecturers in designing innovative and creative learning strategies that are able to support the formation of the character of prospective teachers in a holistic manner